Energy and exergy analyses of combustion process in a DI diesel engine fuelled with diesel-biodiesel blends - Shahnaz Habibian; Rahim Karami; Marziyeh Hoseinpour (Annals of Mathematics and Physics - Peertechz Publications, 2021)
Exergy analysis is achieved by assessing exergies related to the inlet fuel and air, output power, heat loss, gas exhaust loss and destruction or system irreversibility. The exergy fraction of each component is considered for all mixtures by dividing the individual exergy quantity into the exergy of the fuel. In the present investigation, the combustion process has been simulated in a DI diesel engine (OM314) with biodiesel fuel different Blends (B20, B40, B100) of soybean at full load and 1200 rpm by a thermodynamic model using both thermodynamics first and second laws of thermodynamics. The results showed good agreement with the experimental pressure. The results of the analysis of energy and availability balance show that the first and second laws efficiency for pure biodiesel fuel is more than the other two fuel and total availability. indicated work availability, the heat loss availability, burned fuel availability and irreversibility for 20% biodiesel fuel are more than two other fuels.